Asas Itikad Baik dalam Perjanjian Sewa-Menyewa Rumah Kantor - Manaon Damianus Sirait; Johannes Ibrahim Kosasih; Desak Gde Dwi Arini (Jurnal Analogi Hukum, 2020)
The needs of a place which can used for the house, office raising as relating to the economic business growing in any states, The State Union of Republic of Indonesia (NKRI), including. Unrarely, there is a gap between the needs and the property availability which causing the price of leasing raise up or down. The property high demand without a balanced supply can push a new business line up. Now a new business line growing vastly is the leasing business of the house, office, at the cities with a strategic location. The legal fundament of the lease determining in article 1548 of the Civil Code (KUHPerdata). The research method using in the writing of this ascription is the normative law research with conceptual approached by the relevant law materials and law regulations. Leasing as a mutual agreement in which each party ought to perform the substances of the lease agreement to avoid the defaults. According to the research result, there are a few conclusions, namely: First, the law impact of default on leased contract are compensations, cancellation of the agreement, risk transfer, and the payment of case fees. Second, the good faith formulation in leased contract based on article 1320 Co 1338 verses (3) Code of Civil Law (KUHPerdata) that emphasizing trust, good will and full responsibility on their dealing in leased contract. The good faith could be formulated after the parties understood its meaning interpretation and the function in the leased contract.